The tracheal mite Locustacarus buchneri in South American native bumble bees (Hymenoptera: Apidae) - Plischuk, Santiago (2013)
As in other regions of the world, bumble bees (Bombus spp.) are important pollinators in the neotropics. Despite its relevance, knowledge on their health is still limited in the region. While external acari are known to occur in these insects, presence of the internal, tracheal mite Locustacarus buchneri is here reported for first time. After the examination of 2,508 individuals of eight Bombus species from Argentina, two workers of Bombus bellicosus and one of Bombus atratus were found parasitized by L. buchneri in localities within San Luis and Buenos Aires provinces, respectively. The rare occurrence recorded agrees with findings from elsewhere in the world.